Facile Synthesis of ZnO Nanoparticles on Nitrogen-Doped Carbon Nanotubes as High-Performance Anode Material for Lithium-Ion Batteries - Li, Haipeng; Liu, Zhengjun; Yang, Shuang; Zhao, Yan; Feng, Yuting; Bakenov, Zhumabay; Zhang, Chengwei; Yin, Fuxing (Materials, 2017)
ZnO/nitrogen-doped carbon nanotube (ZnO/NCNT) composite, prepared though a simple one-step sol-gel synthetic technique, has been explored for the first time as an anode material. The as-prepared ZnO/NCNT nanocomposite preserves a good dispersity and homogeneity of the ZnO nanoparticles (~6 nm) which deposited on the surface of NCNT. Transmission electron microscopy (TEM) reveals the formation of ZnO nanoparticles with an average size of 6 nm homogeneously deposited on the surface of NCNT. ZnO/NCNT composite, when evaluated as an anode for lithium-ion batteries (LIBs), exhibits remarkably enhanced cycling ability and rate capability compared with the ZnO/CNT counterpart. A relatively large reversible capacity of 1013 mAh_g-1 is manifested at the second cycle and a capacity of 664 mAh_g-1 is retained after 100 cycles. Furthermore, the ZnO/NCNT system displays a reversible capacity of 308 mAh_g-1 even at a high current density of 1600 mA_g-1. These electrochemical performance enhancements are ascribed to the reinforced accumulative effects of the well-dispersed ZnO nanoparticles and doping nitrogen atoms, which can not only suppress the volumetric expansion of ZnO nanoparticles during the cycling performance but also provide a highly conductive NCNT network for ZnO anode.
Keywords: lithium ion battery; anode; ZnO/nitrogen-doped carbon nanotube (ZnO/NCNT) composite; highly-dispersed ZnO nanoparticles; sol-gel; Research Subject Categories::TECHNOLOGY::Materials science